God almighty and god all-loving: a review article of David Ray Griffin's "God exists but Gawd does not" - Viney, Donald Wayne (Process studies, 2016)
Griffin's book contributes to the literature of cumulative arguments for God's existence, revealing the deficiencies of the "God Almighty" of traditional theism (i.e., Gawd) and the strengths of a Whiteheadian process theism (i.e., God). Since the concept of omnipotence is central, it is imperative to note that there are three ideas of divine power in traditional theism, not always carefully parsed by Greffin. Evolutionary theory requires rethinking theism, but, contrary to Griffin, many of the problems posed by the theory are less for belief in Gawd than for fundamentalism. Nevertheless, an interactive dipolar deity fits most naturally with evolutionary thinking to provide a concept of God All-Loving. Griffin is at his best discussing the ground of abstract truths. He does not, however, avail himself of some of the best arguments against traditional theism found in Hartshorne's work; there is also the question whether Griffin would accept Hartshorne's idea of the modal coincidence of God's existence and all possibility and how this would affect his cumulative case.